Individualization of drug therapy in older people. Issue 2 (20th March 2014) - Scibona, P; Angriman, F; Vazquez, C; Ferreyro, BL; Perelsztein, AG; Simonovich, VA; Jauregui, JR; Musso, CG; Belloso, WH
Summary: Older people are high consumers of prescription drugs and are at increasing risk of polypharmacy and adverse reactions. Pharmacokinetic and pharmacodynamic modifications due to age and co-morbidities are an important consideration, but pharmacological background evidence to guide safe and effective therapeutic approaches are often inadequate since the older population is under-represented in clinical trials. We review the pharmacokinetic and pharmacodynamic changes that are characteristic in old age and consider evidence regarding potentially safer prescription and monitoring of drugs commonly used in older patients. We also introduce the possible role of pharmacogenomics and therapeutic drug monitoring as tools to guide the individualization of drug therapy.